1995
DOI: 10.1002/hep.1840220221
|View full text |Cite
|
Sign up to set email alerts
|

The liver in adolescents with α-antitrypsin deficiency

Abstract: Of 200,000 Swedish infants screened for alpha 1-antitrypsin deficiency (alpha 1 ATD), 184 (127 PiZ, 2 PiZ-, 54 PiSZ, and 1 PiS-) children have been followed prospectively, of whom 1 PiSZ and 5 PiZ children died in early childhood. We now report clinical and biochemical signs of liver disease in adolescence and the prognosis of neonatal liver disease up to the age of 18 years. The alpha 1 ATD subjects were offered a clinical checkup and liver tests at 16 and 18 years of age, 150 of 178 alpha 1ATD subjects under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 23 publications
4
84
0
2
Order By: Relevance
“…Prospective nationwide screening studies carried out in Sweden have confirmed that only ϳ10% of this population develops clinically significant liver disease (21,22). Using a genetic complementation approach, we found that there is less efficient ER degradation of ␣1-ATZ in cells from some ␣1-AT-deficient individuals who are susceptible to liver disease (16) and, therein, that these individuals have a lesser inherent capacity to respond to, and/or protect themselves from, the hepatotoxic circumstances posed by ER retention of mutant ␣1-ATZ.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective nationwide screening studies carried out in Sweden have confirmed that only ϳ10% of this population develops clinically significant liver disease (21,22). Using a genetic complementation approach, we found that there is less efficient ER degradation of ␣1-ATZ in cells from some ␣1-AT-deficient individuals who are susceptible to liver disease (16) and, therein, that these individuals have a lesser inherent capacity to respond to, and/or protect themselves from, the hepatotoxic circumstances posed by ER retention of mutant ␣1-ATZ.…”
Section: Discussionmentioning
confidence: 99%
“…Some present in liver failure and require liver transplantation in the first several years of life whereas others do not manifest any clinical signs of liver disease for many years. A prospective nationwide screening study in Sweden has shown that 80-90% of PIZZ individuals identified prospectively have no clinical evidence of liver disease by 18 years of age, their age at the time of the last report on this population (11). Although some of these patients may have subclinical liver injury as evidenced by the fact that cirrhosis and hepatocellular carcinoma can be found incidentally at autopsy in PIZZ individuals who have died of other causes (12), the overwhelming clinical experience with this disease indicates that there is a high degree of genotype-phenotype variation in the effect of ␣1-AT deficiency on the development of liver disease and a number of PIZZ individuals are relatively ''protected'' from liver disease or have very slowly progressing liver disease.…”
mentioning
confidence: 99%
“…One interesting observation, arising from unbiased nationwide screening studies of ␣ 1 -AT deficiency in Sweden, indicates that only 10 -15% of deficient individuals develop clinically significant liver disease (8,9). In previous studies we tested the hypothesis that this subgroup of deficient individuals is susceptible to liver injury by virtue of additional unlinked genetic traits or environmental factors that delay degradation of the mutant ␣ 1 -ATZ molecule after it is retained in the ER (10).…”
mentioning
confidence: 99%